2015
DOI: 10.1007/s10995-015-1895-7
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Physical Activity Intervention: A Randomized Pilot Study in Physically Inactive Pregnant Women

Abstract: Introduction Physical inactivity is prevalent in pregnant women, and innovative strategies to promote physical activity are strongly needed. The purpose of the study was to test a 12-week mobile health (mHealth) physical activity intervention for feasibility and potential efficacy. Methods Participants were recruited between December 2012 and February 2014 using diverse recruitment methods. Thirty pregnant women between 10 and 20 weeks of gestation were randomized to an intervention (mobile phone app plus Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
272
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 167 publications
(281 citation statements)
references
References 27 publications
6
272
0
3
Order By: Relevance
“…After activation, there is an adequate short-and long-term use as well as intention to use these apps [17][18][19][20][21][22][23][24][25]. This is in line with the perceived suitability of the apps that are often judged as good, easy, and simple to use.…”
Section: Mhealth Lifestyle Appsmentioning
confidence: 66%
See 3 more Smart Citations
“…After activation, there is an adequate short-and long-term use as well as intention to use these apps [17][18][19][20][21][22][23][24][25]. This is in line with the perceived suitability of the apps that are often judged as good, easy, and simple to use.…”
Section: Mhealth Lifestyle Appsmentioning
confidence: 66%
“…In total, 10 studies reported on effectiveness of the app [20][21][22][23]28,[31][32][33][34][35]. Moreover, 5 studies reported on smoking cessation [22,23,32,33,35].…”
Section: Results On Effectiveness Of Mhealth Lifestyle Appsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estimating the overall effect size with a reduced pool of outcomes instead of baseline group differences as covariate painted much the same picture (estimated effect size g=. 28 …”
Section: Point Estimatementioning
confidence: 87%